Analysis of existing methods of delivery of fluid cargo in universal containers - Ilesaliev D.I (Научно-технический вестник Брянского государственного университета)
In order to make the best use of the carrying capacity and capacity of universal containers, as well as to ensure rational transshipment and reduce downtime of vehicles, the existing methods of delivering bulk cargoes are analyzed. The advantages and disadvantages of methods ensuring timely handling of cargoes are determined. The subject of the study is the structure of technology for the delivery of bulk cargo transported in containers. The purpose of the study is to improve the delivery system based on a more efficient structure of the supply chain in the field of automated loading and unloading of bulk goods into containers. The research methods are based on the analysis and generalization of the existing methods of collecting the initial information, the methods of its processing in support of the choice of the most rational technology for the transport of loose goods in containers.